METHODOLOGY FOR RESEARCHING OF DEVELOPMENT OF FARMS AND THE EFFICIENCY OF THEIR FUNCTIONING (INNOVATIVE ECONOMY, 2020)
Savka M.V. METHODOLOGY FOR RESEARCHING OF DEVELOPMENT OF FARMS AND THE EFFICIENCY OF THEIR FUNCTIONINGPurpose. The substantiation of the methodology of research on the development and efficiency of farm operation, based on dialectics and economic laws, covers the latest achievements of domestic and foreign economic science.Methodology of research. In the course of research, the author used the following methods: induction, deduction, dialectic method, comparison, graphical method, SWOT analysis, method of optimization and forecasting to assess the state of development and economic analysis of the efficiency of the functioning of farms.The theoretical and methodological basis of the research is dialectic method of cognition, system approach and analysis, fundamental positions of the economy of the domestic agricultural sector.Findings. Literary review of modern views on the methodology of development of farms, the strengths and weaknesses of farms, opportunities and threats that arise in the process of production activity are determined.The analysis provides an opportunity to draw conclusions about the current state and prospects of the development of farms. The organization of economic activity of farms is based on a solid foundation, has a fairly wide legislative base and normative regulation. Determination and analysis of the main conditions for the organization of activity, functioning and development prospects, substantiation of the directions of increase of production volumes, formation of own market of sales of products is the main purpose of creating farms and requires urgent solution of actual problems of their functioning.Originality. The novelty of scientific research results is to substantiate the theoretical, methodological and practical bases of development and efficient functioning of farms, which are an important component of the agrarian sector of the Ukrainian economy, which ensure the efficient use of land and material resources, describes the main types of classification, first of all, the method of systematics, the results of which is a certain grouping of objects on one sign or set of signs.Practical value. The obtained research results allow carrying out researches of development of the farms, analyzing the efficiency of their financial and economic activity and, as a result, determining the main directions of the necessary state support. They can be applied in practical organizational and economic activity of farms.Key words: farming; cooperation; methodology; systematization; SWOT - analysis; land; provision; village; structure; agricultural commodity producer; profitability; development.
Keywords: Key words; farming; cooperation; methodology; systematization; SWOT - analysis; land; provision; village; structure; agricultural commodity producer; profitability; development.